Fatores de risco relacionados às quedas em idosos residentes na comunidade - Rodrigues, Mayara Muniz Peixoto (2017)
Introduction: Aging is characterized by a progressive process and gradually taking as consequence morphological, physiological, biochemical and psychological changes with increase of chronic degenerative diseases and risk of falls. Objective: Analyze the risk of falls in the elderly community residents with the aim to understand their needs and directing the nursing actions in health care practice. Method: A descriptive crosssectional and quantitative approach study developed from June to September 2016 in a town in the northeastern region of Brazil with 221 elderly residents in the community with the use of instruments structured. There was an exploratory analysis, analysis of the association between variables, calculation of sensitivity and specificity of the Fall Risk Score, and its association with the risk factors. This study was approved by the Research Ethics Committee, protocol 0660/15 and CAAE: 51441815.1.0000.5188. Results: There was a prevalence of the elderly between 60 and 79 years, female; married, living with a partner, 1 to 4 years of education, individual income up to 1 monthly minimum wage from retirement, and 3 to 5 self-referred comorbidities. Regarding the risk of falls, stood out the score of the Fall Risk Score, anti-Parkinsonian medicine, hypoglycemia, hearing, diuretic, pain, urinary incontinence, neurological symptoms and antidepressant medicine. In relation to Fall Risk Score there was obtained an accuracy of 77.7%, sensitivity of 75% and specificity 66%, considering the three best scores to the high risk of falls. Individuals with hypertension, heart disease, cancer, cataracts or glaucoma, rheumatism, arthritis or osteoarthritis, memory problems, diabetes mellitus, osteoporosis and back trouble were associated with high risk of falls for Fall Risk Score. Conclusion: It was evidenced the importance of establishing individual and collective actions for prevention and health promotion for the elderly face the risks encountered. It is important that nursing staff meet and get ready for the action on the risk factors of falls among the elderly, more relevant as it allows a better care planning directed to the real needs of this population.